1988
DOI: 10.1007/bf01960230
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on epidermal growth factor receptor level in the rat brain

Abstract: The influence of age on 125I-epidermal growth factor (EGF) binding to rat brain plasma membranes was investigated. The specific binding of EGF to membranes decreased gradually with age in both male and female rats. There was no significant difference in the specific binding between males and females. Scatchard analysis of the binding data showed that the decrease in EGF binding with age was due to a decrease in the number of EGF receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In AD pathology, aggregates and deposits of the protein fragment β -amyloid (plaques) and twisted strands of the protein Tau (neurofibrillary tangles) induce the generation of nerve cell damage and cell death in areas of the brain including the cortex and especially the hippocampus [110, 112–114]. With respect to an association with AD etiology it has been demonstrated that EGFR expression in the rat brain reduces with age both in males and females [115]. AD-related neuritic plaques observed in the cerebral cortex and hippocampus of patients with AD also immunostain positively for EGFR [93].…”
Section: Egfr and Neurodegenerative Diseasementioning
confidence: 99%
“…In AD pathology, aggregates and deposits of the protein fragment β -amyloid (plaques) and twisted strands of the protein Tau (neurofibrillary tangles) induce the generation of nerve cell damage and cell death in areas of the brain including the cortex and especially the hippocampus [110, 112–114]. With respect to an association with AD etiology it has been demonstrated that EGFR expression in the rat brain reduces with age both in males and females [115]. AD-related neuritic plaques observed in the cerebral cortex and hippocampus of patients with AD also immunostain positively for EGFR [93].…”
Section: Egfr and Neurodegenerative Diseasementioning
confidence: 99%
“…Beginning at 15 days after birth, it can be detected in the globus pallidus, endopeduncular nucleus, substantia nigra pars reticulata, ventral pallidum, islands of Calleja complex, and to a lesser extent in the stria terminalis and layers I-V of cerebral cortex of rats (Fallon et al, 1984). The EGF receptor, which also binds transforming growth factor-a (TGF-a) (Marquardt et al, 1983) is also present in mammalian brain (Adamson and Meek, 1984;Gomez-Pinilla et al, 1988;Heldin et al, 1979;Hiramatsu et al, 1988;Leutz and Schachner, 1982;Sadiq et al, 1985;Simpson et al, 1982;Werner et al, 1988). Studies have shown the EGF receptor to be present on glia (Heldin et al, 1979;Simpson et al, 1982;Leutz and Schachner, 1981;Nieto-Sampedro and Broderick, 1989), neurons (Werner et al, 1988), or both (Gomez-Pinilla et al, 1988;Leutz and Schachner, 1982;Wang et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports suggesting that bFGF promotes the survival of mesencephalic DA neurons. Hiramatsu and co-workers (Hiramatsu et al, 1988) reported a gradual decrease in the number of brain EGFR sites in rats during normal aging, although the authors did not determine if the difference was associated with any CNS dysfunction or with the presence of any marker degeneration. EGF receptor (EGFR) binding sites have been found in rodent and human brain (Nexo et al, 1980;Adamson et al, 1981;Sagen and Pappas, 1987;Hiramatsu et al, 1988), and in cells of human brain tumors (Reubi et al, 1989).…”
Section: Types Of Nfs and Their Target Cellsmentioning
confidence: 98%
“…Moreover, additive effects of the two factors cannot be completely excluded (Araujo et al, 1990). EGF receptor (EGFR) binding sites have been found in rodent and human brain (Nexo et al, 1980;Adamson et al, 1981;Sagen and Pappas, 1987;Hiramatsu et al, 1988), and in cells of human brain tumors (Reubi et al, 1989). On the other hand, it is thought that the effects of bFGF are indirect, requiring the presence of glial cells (Ferrari et al, 1989;Knusel et al, 1990), although this data are still controversial ( Walicke and Baird, 1988;Hefti et al, 1989).…”
Section: Types Of Nfs and Their Target Cellsmentioning
confidence: 99%